PERSEPSI MASYARAKAT TERHADAP PEREMPUAN BERSTATUS JANDA - Assyfa Wahida Rachman; Audina Rismayanti Fadlillah; Nur Cholifah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Widow is a status that is obtained by a woman who has been abandoned by her husband, due to divorce or divorce. Women who are already widowed have a tough life. There are differences in society in viewing widows and widowers. In society, the status of a widower is seen as a normal thing and does not always give rise to a negative view. Meanwhile, the status of widows in society has a different view from the status of widowers. This is a gender injustice that still often occurs around us. This article seeks to overcome gender inequality that occurs especially for women who are widows by trying as much as possible, it will not mean to look down on women with that status. Starting from regarding the classification of the status of widows, the heavy burdens they have to carry every day to how widows look from a gender perspective. The connotation of a widow in society is considered an odd label, especially when the widow's status comes from divorce, not from the death of her spouse. The status of a widow due to the death of a spouse is considered slightly more honorable than the status of a widow due to divorce.